Chairman of Board of Directors visits UMP laboratory facilities - Mohd Ferdaus, Musa (2019)
Universiti Malaysia Pahang (UMP)’s laboratory and learning facilities were described as impressive by its Chairman Board of Directors, Dato’ Sri Ibrahim Ahmad who spent about two hours in the Gambang campus on January 22, 2019.